Iatrogenic III° frostbite injury of the breast: clinical case report - Čepas, Adas; Rimdeika, Rytis; Aštrauskaitė, Goda; Žurman, Elina (Lietuvos chirurgija, 2017)
Iatrogenic frostbite injuries are extremely rare in medical practice. According to the latest publications only one iatrogenic frostbite injury of the breast was stated which did not require surgical intervention. We are presenting deep III° frostbite injury of the breast managed conservatively and surgically. This clinical case reports 29 year old breastfeeding patient sustained mastitis symptoms and applied ice packs on her left breast and fell asleep. In two days the patient was admitted to Hospital of Lithuanian University of Health Sciences “Kauno Klinikos” complaining of left breast pain, redness, edema and fever. During the examination erythema, edema and superficial wounds with necrotic tissue were observed on the lower quadrants of the breast. Early stage treatment consisted of daily antiseptic wound dressings and delayed debridement of obviously necrotic tissue. The wound healing was complicated by breast milk secretion to the wound bed. On the 30th day after injury delayed surgery was performed, some of the milk ducts were ligated and the soft tissue defect was covered by surgery. Post-operative period was complicated with Pseudomonas Aeruginosa wound infection. However, adequate antimicrobial therapy coped with wound infection. This clinical case report presents successful treatment of the deep frostbite injury of the breast in breastfeeding patient using delayed debridement and wound plasty.